2021
DOI: 10.1039/d1sc04305f
|View full text |Cite
|
Sign up to set email alerts
|

CsPbBr3–CdS heterostructure: stabilizing perovskite nanocrystals for photocatalysis

Abstract: The instability of cesium lead bromide (CsPbBr3) nanocrystals (NCs) in polar solvents has hampered their use in photocatalysis. We have now succeeded in synthesizing CsPbBr3-CdS heterostructures with improved stability and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 65 publications
4
74
0
Order By: Relevance
“…with free electron exchange and holes migrating toward the MHP), whereby the deposition of a CdS shell could shield the MHP component within a toluene/ethanol mixed solvent, thereby resulting in an improved stability and photocatalytic performance compared with only pristine CsPbBr 3 . [50] A similar stability enhancement in polar solvents was observed by Zhang and co-workers, who found that the Janus CsPbBr 3 /ZrO 2 type II heterojunctions exhibit significant stability enhancement compared with pristine CsPbBr 3 after polar solvent treatment, which is due to the partial coverage of ZrO 2 over CsPbBr 3 . [51] In recent years, various MHP-based type II heterojunctions have been prepared and used in a wide range of chemical reactions, including water splitting, CO 2 reduction reaction, organic transformation, and environmental remediation (Table S2).…”
Section: Mhp-based Type II Heterojunction Photocatalystssupporting
confidence: 73%
See 1 more Smart Citation
“…with free electron exchange and holes migrating toward the MHP), whereby the deposition of a CdS shell could shield the MHP component within a toluene/ethanol mixed solvent, thereby resulting in an improved stability and photocatalytic performance compared with only pristine CsPbBr 3 . [50] A similar stability enhancement in polar solvents was observed by Zhang and co-workers, who found that the Janus CsPbBr 3 /ZrO 2 type II heterojunctions exhibit significant stability enhancement compared with pristine CsPbBr 3 after polar solvent treatment, which is due to the partial coverage of ZrO 2 over CsPbBr 3 . [51] In recent years, various MHP-based type II heterojunctions have been prepared and used in a wide range of chemical reactions, including water splitting, CO 2 reduction reaction, organic transformation, and environmental remediation (Table S2).…”
Section: Mhp-based Type II Heterojunction Photocatalystssupporting
confidence: 73%
“…Additionally, Kamat and co‐workers reported a quasi‐type II CsPbBr 3 ‐CdS core–shell heterojunction (i.e. with free electron exchange and holes migrating toward the MHP), whereby the deposition of a CdS shell could shield the MHP component within a toluene/ethanol mixed solvent, thereby resulting in an improved stability and photocatalytic performance compared with only pristine CsPbBr 3 [50] . A similar stability enhancement in polar solvents was observed by Zhang and co‐workers, who found that the Janus CsPbBr 3 /ZrO 2 type II heterojunctions exhibit significant stability enhancement compared with pristine CsPbBr 3 after polar solvent treatment, which is due to the partial coverage of ZrO 2 over CsPbBr 3 [51] …”
Section: Impact Of Heterojunction Formation On Mhp‐based Photocatalystsmentioning
confidence: 99%
“…The photocatalytic degradation of AAF by TCN ( Figure 5 ) was always higher than by commercial TiO 2 (P25) and pure TiO 2 prepared, which might be attributed to the formation of the TiO 2 /g-C 3 N 4 heterojunction [ 29 , 44 , 45 , 46 , 47 ]. The TCN samples with a 20 doping ratio, 10 °C·min −1 , 550 °C, 6 h in the same three other conditions showed the optimum photocatalytic degradation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, regarding the applications of PNCs in polar environments, which was the main topic of this review, Kamat and co‐workers [ 109 ] have studied the effect of the deposition of CdS nanoparticles decorating CsPbBr 3 PNCs, to increase their stability in polar solvents. The authors claim that optical properties and stability of the nanocrystals are associated to the passivation of surface defects, which also act as a coverage avoiding the direct interaction with polar species.…”
Section: Charge Transfer Kinetics In Pncsmentioning
confidence: 99%